Vagotomy Improves Hypoxic Pulmonary Vasoconstriction in Rats Subjected to Brain Ischemia-Reperfusion Injury - Maryam Naseh; Amirreza Dehghanian; Farzaneh Ketabchi (Iranian Journal of Medical Sciences, 2020)
Background: Pulmonary dysfunction is one of the critical complications of a stroke. However, it remains unclear whether the mechanism is caused by either neurogenic or inflammatory reactions. The present study aimed to determine the effect of cerebral ischemia-reperfusion injury and the role of the vagus nerve on hypoxic pulmonary vasoconstriction (HPV) in rats. Methods: This study was performed at Shiraz University of Medical Sciences, Shiraz, Iran, 2018. Male Sprague Dawley rats (n=56) were divided into four groups, namely the sham, vagotomy (Vag), 1 hour of ischemia followed by 23 hours of reperfusion without vagotomy (I/R) and with vagotomy (I/R+Vag). Neurological deficit scores and total infarct volumes of brains were measured in the I/R and I/R+Vag groups. Pulmonary artery pressure and lung weight were continuously registered during ventilation with normoxic and hypoxic gases in the isolated lungs. The blood gas parameters and the lung malondialdehyde (MDA) level of each group were also evaluated. ANOVA, with Tukey’s post hoc test and t test, was used to compare the variables in the experimental groups. Results: The infarct volume of the brains in the I/R and I/R+Vag groups were similar. HPV in the I/R group was lower than those in the sham and Vag groups, while vagotomy reversed this response in the I/R+Vag group (P=0.004). In the I/R group, PO2 and pH were lower, and PCO2 was higher than those in the sham and Vag groups. The lung MDA level in the I/R group was higher than that in the Vag group (P=0.019). Conclusion: Brain ischemia-reperfusion injury decreased HPV independent of increased MDA in the lung, whereas vagotomy improved HPV by repairing the blood-gas barrier and oxygen sensing.